2019
DOI: 10.1108/jkm-08-2018-0478
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing dynamic capability in teamwork

Abstract: Purpose This study aims to analyze the relationship between the intrinsic characteristics of the teams that perform specialized industrial services in multi-units and dynamic capability. Design/methodology/approach This study was developed from a survey conducted in 188 multi-unit industrial service providers and data were analyzed using the structural equation modeling technique of partial least squares. Findings The results indicate the two constructs act differently on dynamic capability. While the infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(72 citation statements)
references
References 75 publications
1
69
0
2
Order By: Relevance
“…A study by Aitken (2019) provided a programme fit for improving teamwork. Gonzalez and Melo (2019) showed that the intrinsic characteristics of teams act on a dynamic capability.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Aitken (2019) provided a programme fit for improving teamwork. Gonzalez and Melo (2019) showed that the intrinsic characteristics of teams act on a dynamic capability.…”
Section: Discussionmentioning
confidence: 99%
“…Third, make adjustments or renewals, or replace resources and capabilities so that they can become a source of competitive advantage for the company. Fourth, utilize renewed resources and capabilities to formulate and implement strategies in order to gain new competitive advantages (Gonzalez & Melo, 2019). Technological innovation helps companies to build competitive advantages, more effective services and processes, new businesses, and so on (Rashidirad & Salimian, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Third, make adjustments or renewals, or replace resources and capabilities so that they can become a source of competitive advantage for the company. Fourth, utilize renewed resources and capabilities to formulate and implement strategies in order to gain new competitive advantages (Gonzalez & Melo, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Teams high in cohesion show higher levels of satisfaction, trust and attachment within group members, as it creates team spirit. Teamwork facilitates information flow and knowledge exchange, by building strong relationships among team members; thus, teamwork can increase knowledge sharing and learning (Tekleab et al, 2016), so firms can enhance their knowledge-based capabilities, such as absorptive capacity and innovation (Gonzalez and Melo, 2019;Hern andez, 2019). Thus, cohesive teams have the potential to boost firm performance (Ensley et al, 2002).…”
Section: Organizaɵonal Learningmentioning
confidence: 99%
“…Since export departments are exposed to complicated and cross-functional export operations, employees can have excessive responsibilities (Gomez-Mejia, 1988;Navarro-García et al, 2016). Through teamwork, export department employees can effectively undertake their operations, since teamwork improves knowledge sharing, mutual understanding and collaboration not only in the team, but also throughout the organization (Li et al, 2013) that can enhance firm capabilities (Gonzalez and Melo, 2019;Wilden and Gudergan, 2017) and relatedly to export performance (Efrat et al, 2018).…”
Section: Mrr 441mentioning
confidence: 99%